Comparison of the Antibacterial Activity of Orange Peel Eco-Enzyme against Staphylococcus aureus and Escherichia coli - Elisa Rinihapsari; Materius Kristiyanto; Zalsa Billa Lutia Tambora (Media Farmasi Indonesia, 2026)
Orange peel contains various bioactive compounds known to possess antibacterial and antioxidant activities, making it a potential raw material for eco-enzyme production. This study aimed to determine the concentration of orange peel eco-enzyme that exhibits the highest antibacterial activity against Staphylococcus aureus and Escherichia coli, as well as to compare the antibacterial activity of orange peel eco-enzyme against Staphylococcus aureus and Escherichia coli. Another objective was to evaluate differences in antibacterial activity at different incubation times. This study employed an experimental design, involving antibacterial activity testing of orange peel eco-enzyme using the Kirby–Bauer disk diffusion method. The independent variable was the concentration of orange peel eco-enzyme at 70%, 80%, 90%, and 100%. Other independent variables included bacterial species and incubation times of 18 and 24 hours. The overall statistical analysis showed that the eco-enzyme exhibited significant antibacterial activity against both Staphylococcus aureus and Escherichia coli, with the optimal concentration being 90%. The Mann–Whitney test indicated no significant difference in antibacterial activity between Staphylococcus aureus and Escherichia coli (p > 0.05). Comparison between incubation periods of 18 and 24 hours also revealed no significant difference in antibacterial activity (p > 0.05), indicating that the orange peel eco-enzyme has good stability of antibacterial activity against both test bacteria.